A practical guide on the use of imiquimod cream to treat lentigo maligna. (16th September 2021) - Guitera, Pascale; Waddell, Andreanne; Paton, Elizabeth; Fogarty, Gerald B; Hong, Angela; Scolyer, Richard A; Stretch, Jonathan R; O'Donnell, Brett A; Pellacani, Giovanni
Abstract: Lentigo maligna (LM) is a common in situ melanoma subtype arising on chronically sun‐damaged skin and mostly affects the head and neck region. Localisation in cosmetically sensitive areas, difficulty to obtain wide resection margins and advanced patient age/comorbidities have encouraged investigation of less invasive therapeutic strategies than surgery in managing complex cases of LM. Radiotherapy and imiquimod have emerged as alternative treatment options in this context. The treatment of LM with imiquimod cream can be challenging due to the nature of the disease including its often large size, variegated appearance, involvement of adnexal structures, poorly defined peripheral edge and frequent localisation close to sensitive structures such as the eyes and lips, and elderly patients with multiple comorbidities. Prolonged and unpredictable inflammatory reaction and side effects and compliance with a patient‐delivered therapy can also be challenging. In the literature to date, studies evaluating the use of imiquimod to treat LM have utilised varying methodologies and provided short follow‐up and these limitations have impaired the development of clear guidelines for dosage and management of side effects. Based on our multidisciplinary experience and review of the literature, we propose practical clinical strategies for the use of imiquimod for treating LM, detailing optimal administration procedures in various clinical scenarios and long‐term management, with the aim of facilitating optimal patient outcomes.